(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article analyzes the specific features of reproductive dysfunction in patients with type 1 diabetes mellitus residing in iodine-deficient endemic areas, examining the underlying pathogenetic mechanisms and clinical consequences. The study demonstrates that concurrent hyperglycemia, hypothyroidism, and disruption of the hypothalamic-pituitary-gonadal axis exert a synergistic negative effect on reproductive health in both male and female patients.